Farmer and Veterinary Practices and Opinions Related to the Diagnosis of Mastitis and Metabolic Disease in UK Dairy Cows - Donadeu, Francesc X.; Howes, Natalie L.; Esteves, Cristina L.; Howes, Martin P.; Byrne, Tim J.; Macrae, Alastair I. (Frontiers in Veterinary Science, 2020)
Production diseases are highly prevalent in modern dairy herds, resulting in lost productivity and reduced animal welfare. Two important production diseases are mastitis and metabolic disorders. The availability of robust diagnostic tools that can detect animals at early stages of disease is crucial to prevent the high costs associated with lost productivity and the treatment of clinically and/or chronically diseased animals. Despite a variety of diagnostic methods being available to farmers and veterinarians, the incidence of these diseases in UK dairy herds has not changed over the last decade, underscoring the need for improved approaches for early disease detection. To this end, we administered a questionnaire to farmers and veterinarians to understand current diagnostic practices in the UK dairy cow sector, and to gather opinions on the suitability of currently available diagnostic tests in order to identify specific areas where improvement in diagnostic technologies and/or practices are needed. Data from a total of 34 farmers and 42 veterinarians were analysed. Results indicated that most farmers surveyed used a combination of methods to diagnose mastitis and metabolic disorders, the most popular of which were visual inspection and milk recording somatic cell count data for mastitis, and body condition score and milk ketone testing for metabolic disorders. These preferences were not always in line with veterinarian recommendations of different diagnostic tools. Moreover, veterinarians indicated they were not satisfied with currently available diagnostic tools or how these were implemented by farmers. Both farmers and veterinarians recognised there was substantial room for improvement of current diagnostic tools, particularly in regard to the need to detect disease early. A majority of respondents preferred new diagnostic tests to be suitable for use with milk rather than blood or urine samples, and to yield results within 24 h. Finally, both groups surveyed identified economic cost as the most important barrier for the future uptake of new diagnostic technologies. The information obtained should guide the future development of diagnostic approaches that meet both the expectations of farmers and veterinarians, and help bring about a reduction in the incidence of production diseases in UK dairy herds.